Structural properties of zirconia doped with some oxides - Abbas, Hussien Ahmed; Hamad, Fadwaa Fwad; Mohamad, Atrees Khair; Hanafi, Zeinab Mohamad; Kilo, Martin (Diffusion Fundamentals, 2008)
Zirconia powders doped with different amounts of dopants (CeO2, Gd2O3, and CaO) were synthesized by a citrate technique. X-ray diffraction for samples sintered at 1500 °C revealed that the zirconia ceramics were stabilized in the cubic phase above 12 mole % CaO and 10 mole % Gd2O3, while tetragonal zirconia is obtained above 15 mole % CeO2. Relative densities up to 99.5% were obtained. The effect of dopant concentration on the lattice parameter, average crystallite size, microstrain was studied. The cubic lattice parameter increases nearly linearly with increasing the concentration in case of CaO and Gd2O3. The tetragonal lattice parameters at and ct increase nearly linearly with increasing the concentration of CeO2. The average crystallite size was found to be larger than 600 nm for the samples investigated.